AudioTrace: business plan - Mohd Sallehuddin, Izad Shahadi (2019)
AudioTrace is a company that facilitates the transformation of a visitor’s experience to an attraction by allowing organizations and third party authors to build customized audio tours on its platform for free. No longer would visitors need to carry a travel book around or google for information on an attraction, as it will all be made available at your fingertips through an app and its website. AudioTrace also provides the service to set up the conventional audio tours for attractions for a fee with an ultimate aim to drive traffic onto its platform.